Land tenure and the management of land and trees: the case of customary land tenure areas of Ghana - Otsuka, Keijiro; Quisumbing, Agnes R.; Payongayong, Ellen; Aidoo, J. B. (Cambridge University Press, 2003)
This study explores the effects of land tenure institutions on land use and management using household date from cocoa growing areas of Ghana. Various land tenure institutions with different land rights coexist in our sites, such as allocated family land, inherited land, appropriated village land, and land received as gift. While tree planting and the decision to leave land fallow may be affected by land tenure status, there are no significant differences in labor allocation and revenue of both cocoa and food crops among parcels under different land tenure institutions. These results support the hypothesis that management incentives of cocoa fields, but not food crop fields, tend to be equalized due to the incentive-enhancing effects of granting secure land rights after efforts to plant cocoa trees are expended.